Trump, Johnson and New Primitivism - The Manifestations and Causes of Major Crisis in the USA and the UK - Ognjen Pribićević (Etnoantropološki Problemi, 2022)
Over the past few decades, major changes have taken place in the two most influential Western countries – the USA and the UK. These changes found political expression in Trump’s presidential victory and the triumph of Brexit in 2016. The purpose of this paper is to analyze the changed political reality in these states and explain its causes. In the first part, the author provides a theoretical framework and discusses the old and new categories to provide explanation for the changes in these states. In the second part, he analyzes the main changes in political life in the USA and UK embodied in Donald Trump and British Prime Minister Boris Johnson. In the third part, he points to the basic causes of the crisis in the USA and UK that led to Donald Trump’s victory in 2016 and UK’s withdrawal from the EU.